Analisis Resistensi Pegawai Terhadap Perubahan Kebijakan Pemberian Kompensasi Kepada Karyawan Bagian Teknik pada Perusahaan Umum Daerah Air Minum Tirta Umbu Kabupaten Nias - Lisbet Rostiani Laoli; Ayler Beniah Ndraha; Eliyunus Waruwu (Dinasti Review, 2024)
This study aims to analyze employee resistance to changes in compensation policy at the Regional Public Water Company Tirta Umbu, Nias Regency. The background of this problem is employee dissatisfaction caused by changes in compensation policies that are considered unfair and not transparent. The research method used is descriptive with a qualitative approach, collecting data through interviews, observation, and documentation. The results showed that employee resistance was caused by perceptions of unfairness, policy uncertainty, and lack of effective communication from management. This has a negative impact on employee productivity and loyalty. In conclusion, to overcome the resistance, management needs to increase transparency and fairness in compensation policy, clarify incentive criteria, and improve communication through socialization sessions and employee involvement in the decision-making process. Additional support and training for employees is also recommended to reduce apprehension and improve adaptation to change.